INTEGRATION OF PEGON ARABIC ORTHOGRAPHIC LEARNING IN GORONTALO'S LOCAL WISDOM-BASED CURRICULUM: A NEEDS ANALYSIS - Ibnu Rawandhy N. Hula; Ana Mariana (LP2M IAIN Sultan Amai Gorontalo, 2024)
The Orthography of Arab Pegon in Gorontalo is very important to study, but it has not yet been integrated into the curriculum based on local cultural wisdom. This research aims to answer three questions: (1) How is the analysis of students' needs related to difficulties in learning Arab Pegon Orthography in the context of local wisdom? (2) How is the evaluation of educational institutions' readiness to implement Arab Pegon Orthography in a curriculum based on local wisdom? (3) What are the strategic recommendations for integrating Arab Pegon Orthography into the curriculum of educational institutions in Gorontalo? The research method uses a mixed approach, with data collected through surveys, interviews, and observations. The sample consists of 50 students, 20 teachers, and 5 managers of pesantren in Gorontalo. The results of the study show that the evaluation data on the difficulties of teaching Arab Pegon Orthography in Gorontalo are not normally distributed, necessitating non-parametric statistical methods through the Kruskal-Wallis test, which indicates no significant differences among the indicators of Fluency, Pronunciation, Writing, and Comprehension, suggesting that the performance among groups is relatively similar. The Mann-Whitney U Test comparison shows that Hubulo excels if there are significant differences. The evaluation of institutional readiness shows that 60% have adequate infrastructure, while 40% need improvement and 60% of institutions have competent teachers. Strategic recommendations include (1) curriculum integration with local wisdom, (2) regular training for teachers, (3) partnerships with higher education institutions, and (4) the use of technology in learning, aimed at addressing challenges and enhancing students' love for reading, writing, and understanding the Orthography of Arab Pegon in Gorontalo.